PROTEOMIC ANALYSIS OF URINARY PROTEIN MARKERS FOR PREDICTING DIABETIC KIDNEY DISEASE - Omonov Akmal Abdisalimovich; Pardabayeva S. Z.; Mamasoatov O. Sh.; Uzoqboyeva R. Q.; Sayfullayeva O. B.; Soataliyeva R. Sh. (Modern American Journals, 2026)
Diabetic kidney disease (DKD) is a common microvascular complication, affecting 20–40% of individuals diagnosed with type 2 diabetes, leading to high morbidity and mortality rates. DKD is diagnosed based on persistent proteinuria, an albumin-to-creatinine ratio exceeding 30 mg/g creatinine, decreased estimated glomerular filtration rate (eGFR), and progressive decline in renal function. Identifying biomarkers of renal functional damage that can predict kidney disease at early stages and monitor disease progression remains a pressing issue.
Keywords: Serum zinc-alpha-2-glycoprotein (ZAG), diabetic nephropathy (DN), albumin, urinary ZAG, mg/g creatinine, eGFR.